The Synergy of Local Wisdom and National Law in Environmental Law Enforcement: A Qualitative Study in Indigenous Communities - Nugroho, Aldhy Bintang; Ningtiyas, ⁠Hanna Ade; Nurramdani, Husni; M, Nabila Dyahayu; K, Rachmasari Anna; FR, Mella Ismelina (Journal of English Language and Education, 2025)
Environmental degradation in Indonesia, driven by deforestation, land degradation, and uncontrolled exploitation of natural resources, requires an environmental law enforcement strategy that goes beyond national regulations and recognizes the essential role of indigenous local wisdom. This study aims to analyze the contribution of local wisdom to environmental preservation, identify challenges in the implementation of national law in indigenous territories, and formulate a synergy model between the two to strengthen environmental law enforcement. A qualitative approach with a case study method was employed, focusing on indigenous communities that actively practice traditional resource management. Data were collected through in-depth interviews, participatory observations, and document analysis of national regulations and customary laws. The findings reveal that local wisdom effectively maintains ecological balance through culturally rooted governance systems, yet its formal legal recognition remains limited, creating a gap between state policy and local practices. Strengthening the synergy between national law and local wisdom is essential to establish a more participatory, just, and sustainable environmental law enforcement system and to enhance the social legitimacy of environmental policies.